2016
DOI: 10.1016/j.vetpar.2016.03.027
|View full text |Cite
|
Sign up to set email alerts
|

Coadministration of nematophagous fungi for biological control over gastrointestinal helminths in sheep in the semiarid region of northeastern Brazil

Abstract: This study aimed to evaluate coadministration of Duddingtonia flagrans and Monacrosporium thaumasium in a sodium alginate matrix for controlling gastrointestinal helminths in young and adult sheep in the semiarid region of northeastern Brazil. An area of 1ha was divided into two paddocks, in which two experimental groups (fungus and control) were formed, each consisting of six adult females and ten young males. In each group, two subgroups were formed in accordance with the animal category (adult or young). In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
1
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 20 publications
0
16
1
1
Order By: Relevance
“…In this group, on day 180, the fecal egg count reduction was 80%, compared with the control group. Vilela et al (2016) coadministered pellets of D. flagrans and Monacrosporium thaumasium to sheep in the semiarid region of Paraíba under the same grazing pressure. They observed that statistical differences in EPG counts (p < 0.05) only started at the 60 th day of the experiment, with a fecal egg count reduction on day 180 that was similar to what was seen in the present study (76% in adults and 83% in juveniles).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this group, on day 180, the fecal egg count reduction was 80%, compared with the control group. Vilela et al (2016) coadministered pellets of D. flagrans and Monacrosporium thaumasium to sheep in the semiarid region of Paraíba under the same grazing pressure. They observed that statistical differences in EPG counts (p < 0.05) only started at the 60 th day of the experiment, with a fecal egg count reduction on day 180 that was similar to what was seen in the present study (76% in adults and 83% in juveniles).…”
Section: Discussionmentioning
confidence: 99%
“…Silva et al (2009) also did not observe any significant changes to the weights of sheep that underwent treatment with pellets containing D. flagrans and Monacrosporium thaumasium in southeastern Brazil, probably because these were adult animals that were receiving a weight maintenance diet. In a study testing the efficacy of pellets of D. flagrans and M. thaumasium that were coadministered to juvenile sheep, Vilela et al (2016) observed a statistical difference from the 90 th day of the experiment onwards, with a mean weight gain of 18.7 kg at day 180, while the control had a gain of 8.1 kg.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tem ação hematófaga, causando grave anemia e levando o animal a morte (Vilela et al 2012, Vieira et al 2014a. Em ovinos, além de H. contortus, Trichostrongylus columbriformis, Strongyloides papillosus e Oesophagostomum columbianum também são considerados causadores de prejuízos nessa região (Vieira et al 2014b, Vilela et al 2016.…”
Section: Introductionunclassified
“…The coadministration of Duddingtonia flagrans and Monacrosporium thaumasium has been effective in controlling gastrointestinal helminths of adults and young sheep (Vilela et al, 2016).…”
Section: Sustainable Controlmentioning
confidence: 99%